ChemInform Abstract: Ferromagnetism of Zinc Oxide Nanograined Films. Issue 37 (16th September 2014) - Straumal, B. B.; Protasova, S. G.; Mazilkin, A. A.; Schuetz, G.; Goering, E.; Baretzky, B.; Straumal, P. B.
Abstract Review: 33 refs.